Effects of pramipexole on the processing of rewarding and aversive taste stimuli. - Mccabe, C; Harwood, J; Brouwer, S; Harmer, C; Cowen, P (2013)
RATIONALE: Pramipexole, a D2/D3 dopamine receptor agonist, has been implicated in the development of impulse control disorders in patients with Parkinson's disease. Investigation of single doses of pramipexole in healthy participants in reward-based learning tasks has shown inhibition of the neural processing of reward, presumptively through stimulation of dopamine autoreceptors. OBJECTIVES: This study aims to examine the effects of pramipexole on the neural response to the passive receipt of rewarding and aversive sight and taste stimuli. METHODS: We used functional magnetic resonance imaging to examine the neural responses to the sight and taste of pleasant (chocolate) and aversive (mouldy strawberry) stimuli in 16 healthy volunteers who received a single dose of pramipexole (0.25 mg) and placebo in a double-blind, within-subject, design. RESULTS: Relative to placebo, pramipexole treatment reduced blood oxygen level-dependent activation to the chocolate stimuli in the areas known to play a key role in reward, including the ventromedial prefrontal cortex, the orbitofrontal cortex, striatum, thalamus and dorsal anterior cingulate cortex. Pramipexole also reduced activation to the aversive condition in the dorsal anterior cingulate cortex. There were no effects of pramipexole on the subjective ratings of the stimuli. CONCLUSIONS: Our results are consistent with an ability of acute, low-dose pramipexole to diminish dopamine-mediated responses to both rewarding and aversive taste stimuli, perhaps through an inhibitory action of D2/3 autoreceptors on phasic burst activity of midbrain dopamine neurones. The ability of pramipexole to inhibit aversive processing might potentiate its adverse behavioural effects and could also play a role in its proposed efficacy in treatment-resistant depression.